2008
DOI: 10.1093/schbul/sbm153
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Flush Response to Niacin Skin Patch Among Schizophrenia Patients and Their Nonpsychotic Relatives: The Effect of Genetic Loading

Abstract: We previously reported familial aggregation in flush response to niacin skin patch among schizophrenia patients and their nonpsychotic relatives. However, little is known about whether this abnormal skin response is associated with genetic loading for schizophrenia. This study compared the niacin flush response in subjects from families with only one member affected with schizophrenia (simplex families) with those from families having a sib-pair with schizophrenia (multiplex families). Subjects were patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 44 publications
2
29
0
1
Order By: Relevance
“…The data indicate that genetic background affects the flush response to niacin (14). In contrast to these studies, and consistent with our findings, the study by Smesny et al found no impaired niacin skin response in relatives of schizophrenic patients (16).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The data indicate that genetic background affects the flush response to niacin (14). In contrast to these studies, and consistent with our findings, the study by Smesny et al found no impaired niacin skin response in relatives of schizophrenic patients (16).…”
Section: Discussionsupporting
confidence: 91%
“…In the study by Liu et al, also the greatest degree of differentiation occurred at the 0.01 M concentration, but with the rating time point of 10 minutes (18). However, in the study by Change et al, the differentiation was better using 0.1 M compared to 0.01 M or 0.001 M concentrations of niacin (14). The skin flush response evaluation method also can affect the test properties and the optimal solution concentration and evaluation time point (29).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, it appears that nicotine use has no effect on the niacin-induced flushing response (Chang et al, 2009;Liu et al, 2007;Messamore, 2003Messamore, , 2010Ross et al, 2004;Shah et al, 2000;Smesny et al, 2003). Our recent findings (Yao et al, 2015) also support the notion that niacin sensitivity is not significantly affected by smoking.…”
Section: The Niacin Response Abnormality Is Not An Artifact Of Medicasupporting
confidence: 77%
“…If such drugs do tend to normalize niacin sensitivity, then the potential bias in patient sample would be to underestimate the prevalence or magnitude of the niacin response abnormality in SZ. Taken together, comparing the niacin-induced flushing between medicated and unmedicated SZ patients, or unmedicated, non-psychotic relatives, suggests that the niacin response abnormality in SZ is not an artifact of antipsychotic medications (Chang et al, 2009;Lin et al, 2007;Maclean et al, 2003;Shah et al, 2000).…”
Section: The Niacin Response Abnormality Is Not An Artifact Of Medicamentioning
confidence: 99%